Chromosomal localization of murine interleukin-1 alpha and beta genes. - Boultwood, J; Breckon, G; Birch, D; Cox, R (1989)
DNA analyses of mouse X Chinese hamster somatic cell hybrids and of recombinant inbred mouse strains have previously shown that the interleukin-1 alpha and beta genes are tightly linked on murine chromosome 2, approximately 4.7 cM distal to beta-2-microglobulin. In this study, using in situ chromosome hybridization, we show that the two interleukin-1 genes are located in the F region of murine chromosome 2 and discuss this physical map position in relation to conserved genetic linkage groups.